2011
DOI: 10.1016/j.semcdb.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pharmacology in a simple model system: Implicating MAP kinase and phosphoinositide signalling in bipolar disorder

Abstract: Understanding the mechanisms of drug action has been the primary focus for pharmacological researchers, traditionally using rodent models. However, non-sentient model systems are now increasingly being used as an alternative approach to better understand drug action or targets. One of these model systems, the social amoeba Dictyostelium, enables the rapid ablation or over-expression of genes, and the subsequent use of isogenic cell culture for the analysis of cell signalling pathways in pharmacological researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 104 publications
0
28
0
Order By: Relevance
“…In Dictyostelium discoideum, which serves as a powerful model for studying animal cell motility (4,6,20,34,41,42,43,45,50,82,87,86,92,98), either extracellular K ϩ or Ca 2ϩ at an optimum concentration of 40 mM or 20 mM, respectively, enhances most aspects of basic cell motility in the absence of chemoattractant, including cell elongation, uropod formation, the suppression of lateral pseudopod formation, velocity, directional persistence, and localization of myosin II in the posterior cell cortex (51,78). These facilitating concentrations of K ϩ or Ca 2ϩ cannot be replaced with other monovalent or divalent cations (51) and are within the range of the soluble concentrations of the two cations found in soil (1,5,32,44,49,56) and manure (9,66,83), two common niches in which soil amoebae thrive (12,27,35,67,71).…”
Section: Extracellular Camentioning
confidence: 99%
“…In Dictyostelium discoideum, which serves as a powerful model for studying animal cell motility (4,6,20,34,41,42,43,45,50,82,87,86,92,98), either extracellular K ϩ or Ca 2ϩ at an optimum concentration of 40 mM or 20 mM, respectively, enhances most aspects of basic cell motility in the absence of chemoattractant, including cell elongation, uropod formation, the suppression of lateral pseudopod formation, velocity, directional persistence, and localization of myosin II in the posterior cell cortex (51,78). These facilitating concentrations of K ϩ or Ca 2ϩ cannot be replaced with other monovalent or divalent cations (51) and are within the range of the soluble concentrations of the two cations found in soil (1,5,32,44,49,56) and manure (9,66,83), two common niches in which soil amoebae thrive (12,27,35,67,71).…”
Section: Extracellular Camentioning
confidence: 99%
“…However, the social amoeba Dictyostelium discoideum is the simplest model organism that possesses two presenilin proteins as well as the other three components of the c-secretase complex (Boeckeler and Williams, 2007;McMains et al, 2010). Dictyostelium has been extensively used in a range of motility (Janetopoulos and Firtel, 2008), developmental (Loomis and Shaulsky, 2011) and biomedical studies (Chang et al, 2012;Francione and Fisher, 2011;Ludtmann et al, 2011;Myre et al, 2011;Terbach et al, 2011), and has a number of experimental advantages over existing models (Williams et al, 2006). In this study, we employ the advantages of Dictyostelium to explore the role of the human presenilin 1 protein (PSEN1) in development.…”
Section: Introductionmentioning
confidence: 99%
“…We have employed Dictyostelium to understand the molecular mechanisms underlying VPA action in regards to both putative bipolar-disorder- and epilepsy-related signalling effects (Boeckeler et al, 2006; Eickholt et al, 2005; Williams et al, 1999; Williams et al, 2002; Xu et al, 2007; Ludtmann et al, 2011), and to study the mechanisms of uptake (Terbach et al, 2011). Our previous work has shown that, in Dictyostelium , both VPA and a structurally unrelated bipolar disorder treatment, lithium, chronically reduce the levels of inositol phosphate {e.g.…”
Section: Introductionmentioning
confidence: 99%